2009
DOI: 10.1007/s10562-009-9994-y
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of Formic Acid Oxidation on Highly Dispersed Carbon Supported Pd–TiO2 Electrocatalyst

Abstract: The highly dispersed carbon supported Pd-TiO 2 catalyst was prepared by a liquid phase reduction method with intermittent microwave irradiation. The kinetic parameters, such as the charge transfer parameter (a) and the apparent diffusion coefficient (D) of formic acid electrooxidation on a carbon supported Palladium Titanium dioxide (Pd-TiO 2 /C) electrode were obtained under the quasi steady-state conditions. The dependence on temperature of the formic oxidation at a Pd-TiO 2 /C electrode was also investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 33 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…It was reported that Pd/C exhibited much better activity compared with Pt/C, however, the activity was not satisfactory and more importantly the durability of Pd/C catalyst was in urgent needed for further improvement. Generally, formic acid oxidation on Pd or Pt surface follows a dual pathway mechanism, namely, a dehydration pathway [42][43][44]:…”
Section: Pd-based Catalysts For the Direct Formic Acid Fuel Cells (Dfmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that Pd/C exhibited much better activity compared with Pt/C, however, the activity was not satisfactory and more importantly the durability of Pd/C catalyst was in urgent needed for further improvement. Generally, formic acid oxidation on Pd or Pt surface follows a dual pathway mechanism, namely, a dehydration pathway [42][43][44]:…”
Section: Pd-based Catalysts For the Direct Formic Acid Fuel Cells (Dfmentioning
confidence: 99%
“…Additionally, TiO2 can facilitate the dispersion of noble metal nanoparticles to anchor them. Based on the theory that TiO2 nanoparticles in the catalyst can adsorb OHads species and promote the oxidation reaction on the electrode, Xu et al [44] prepared highly dispersed carbon supported Pd-TiO2 catalyst with intermittent microwave irradiation. The activity of Pd-TiO2/C catalyst for the oxidation of formic acid was higher than that of the Pd/C catalyst [106].…”
Section: Pd Supported On Oxidesmentioning
confidence: 99%
“…In particular, Pd and Pd-based catalysts were widely studied [17][18][19][20]. Although the number of published papers regarding the effects of transition-metal oxides is not as large as for Pt and Pt-based catalysts, enhancing effects of TiO 2 [21][22][23][24][25][26], CeO 2 [27][28][29] and other oxide supports [30][31][32][33][34][35] were reported for Pd.…”
Section: Introductionmentioning
confidence: 99%
“…6 Therefore, it is expected that the catalytic activity of Ag@Pd core-shell nanocatalysts for formic acid decomposition in an aqueous solution can also be promoted by loading Ag@Pd core-shell nanocatalysts on TiO 2 . 6 Therefore, it is expected that the catalytic activity of Ag@Pd core-shell nanocatalysts for formic acid decomposition in an aqueous solution can also be promoted by loading Ag@Pd core-shell nanocatalysts on TiO 2 .…”
Section: Introductionmentioning
confidence: 99%